Analisis efektivitas penerapan software accurate online dalam penyajian data laporan keuangan di PT. Jordan Beauty Products - Nilvia, Ury; Wijayanti, Rini (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aims to analyze the effectiveness of implementing Accurate Online software in presenting financial reports at PT. Jordan Beauty Products. Previously, the company used Microsoft Excel which was considered less efficient and often caused recording errors. Accurate Online was chosen to increase efficiency, accuracy and quality of financial reporting. This research uses a qualitative method with a case study approach. Data was obtained through in-depth interviews, observation and document analysis. The research results show that Accurate Online provides time efficiency of up to 40%, increases report accuracy, and makes tax and inventory management easier. The real-time feature allows management to monitor finances at any time. In conclusion, Accurate Online is effective in improving the quality of financial reports and is relevant to be applied to similar companies.